White matter lesions: age-adjusted values for cognitively healthy and demented subjects - Hentschel, Frank; Damian, Marinella; Krumm, Bertram; Frölich, Lutz (Acta neurologica Scandinavica, 2007)
Objective - To develop age-adjusted norms for white matter lesions (WML) and to differentiate dementia from mild cognitive impairment and normal aging. Materials and methods - 240 patients underwent a comprehensive clinical, neuropsychological and MRI examination. A scale was developed quantify WML in anatomically defined regions by rating size and frequency. FLAIR sequences were used to determine a global and a frontal score. The scores were correlated with the psychometric test results and the final clinical diagnosis: cognitively normal (CN), mild cognitive impairment (MCI), Alzheimer's Disease (AD), vascular dementia (VD). Age-adjusted curves for WML scores were calculated by means of a non-parametic smoothing method. Results - WML scores of the whole cerebrum and the frontal lobe were significantly increased in vascular dementia as compared to CN, MCI and AD. Individual WML scores correlated significantly with age and neuropsychological test results. For the age range 55-72, the WML scores of VD were significantly different from those of CN, MCI and AD. Conclusions - Age-corrected WML load was significantly higher in vascular dementia as compared to MCI, AD and cognitively normals over a wide age range.
Gesehen am 19.10.2020